No. 24. An act in addition to An Act, (approved January 30th, 1835,) entitled An Act to prevent any person in this Territory from carrying arms secretly, §1 (10 Feb., 1838). - (:unkn) unknown (General Publisher, 1838)
it shall not be lawful for any person or persons in this Territory to vend dirks, pocket pistols, sword canes, or bowie knives, until he or they shall have first paid to the treasurer of the county in which he or they intend to vend weapons, a tax of two hundred dollars per annum, and all persons carrying said weapons openly shall pay to the officer aforesaid a tax of ten dollars per annum;
--
Keywords: LICENSE - DEALERS; TAX - PROPERTY OR SALES